PERLINDUNGAN HUKUM OLEH NEGARA INDONESIA TERHADAP LINGKUNGAN DAN KESETARAAN GENDER LEGAL PROTECTION BY THE STATE OF INDONESIA TOWARDS THE ENVIRONMENT AND GENDER EQUALITY - Mohammad Al'rainier Geraldine (Magister Hukum Universitas Semarang, 2023)
This research is prepared with the aim of assisting the national interests of Indonesia by examining legal protection for the environment and gender equality in the context of the expansion of the economy resulting from the implementation of a free-trade agreement. Considering the situation in the ICA-CEPA negotiations, where Canada demands that Indonesia commit to legal protection for the environment and gender equality in the context of the FTA before the agreement can be ratified, and considering that there is no juridical research examining Indonesia's commitments in these relevant issues, it becomes urgent to conduct this research to support the country in obtaining its national interests in ICA-CEPA. This research uses the juridical-normative research method with a statute approach and employs the legal material collection method of literature study as well as the qualitative analysis method. The research findings show that Indonesia has legal protection for the environment in the context of the FTA through the ISPO mechanism and provisions in the IE-CEPA. Regarding gender equality, Indonesia has legal protection through its membership in CEDAW and various applicable national legal instruments, as well as through cooperation with EFTA in women's entrepreneurship. The lack of knowledge (research gap) regarding the law creates an urgency for this research to fill that gap and help Indonesia. Here lies the novelty of the research, namely in complementing previous research to answer unanswered questions.